Molecular mechanisms responsible KPC-135-mediated resistance to ceftazidime-avibactam in ST11-K47 hypervirulent Klebsiella pneumoniae - Qingyu Shi; Siquan Shen; Chengkang Tang; Li Ding; Yan Guo; Yang Yang; Shi Wu; Renru Han; Dandan Yin; Fupin Hu (Emerging Microbes and Infections)
Ceftazidime-avibactam resistance attributable to the blaKPC-2 gene mutation is increasingly documented in clinical settings. In this study, we characterized the mechanisms leading to the development of ceftazidime-avibactam resistance in ST11-K47 hypervirulent Klebsiella pneumoniae that harboured the blaKPC-135 gene. This strain possessed fimbriae and biofilm, demonstrating pathogenicity. Compared with the wild-type KPC-2 carbapenemase, the novel KPC-135 enzyme exhibited a deletion of Glu168 and Leu169 and a 15-amino acid tandem repeat between Val262 and Ala276. The blaKPC-135 gene was located within the Tn6296 transposon truncated by IS26 and carried on an IncFII/IncR-type plasmid. Compared to the blaKPC-2-positive cloned strain, only the MIC of ceftazidime increased against blaKPC-135-positive K. pneumoniae and wasn’t inhibited by avibactam (MIC 32 μg/mL), while clavulanic acid and vaborbactam demonstrated some inhibition. Kinetic parameters revealed that KPC-135 exhibited a lower Km and kcat/Km with ceftazidime and carbapenems, and a higher (∼26-fold) 50% inhibitory concentration with avibactam compared to KPC-2. The KPC-135 enzyme exerted a detrimental effect on fitness relative to the wild-type strain. Furthermore, this strain possessed hypervirulent determinants, which included the IncHI1B/FIB plasmid with rmpA2 and expression of type 1 and 3 fimbriae. In conclusion, we reported a novel KPC variant, KPC-135, in a clinical ST11-K47 hypervirulent K. pneumoniae strain, which conferred ceftazidime-avibactam resistance, possibly through increased ceftazidime affinity and decreased avibactam susceptibility. This strain simultaneously harboured resistance and virulence genes, posing an elevated challenge in clinical treatment.